2021
DOI: 10.1142/s0219455421501273
|View full text |Cite
|
Sign up to set email alerts
|

A New Damage Index Based on Statistical Features, PCA, and Mahalanobis Distance for Detecting and Locating Cables Loss in a Cable-Stayed Bridge

Abstract: Cable-stayed bridges are widely used all around the world. Unfortunately, during their service life, they are exposed to adverse conditions that may cause their deterioration and, consequently, their collapse. Vibration-based structural health monitoring techniques have become the most promising alternatives for efficiently detecting and locating damage into civil structures. In this regard, this paper presents a new methodology based on statistical features, Principal component analysis (PCA), and Mahalanobis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Dynamic damage identification methods also include damage identifications that are based on signal processing [11][12][13] and damage identification based on statistical characteristics of the dynamic response. The latter utilizes statistical theory for damage detection directly in the time domain, and compared with other dynamic-based damage identification methods, this method is operationally simple and does not involve a complex modal processing procedure, which does not result in the loss of valid information.…”
Section: Of 23mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic damage identification methods also include damage identifications that are based on signal processing [11][12][13] and damage identification based on statistical characteristics of the dynamic response. The latter utilizes statistical theory for damage detection directly in the time domain, and compared with other dynamic-based damage identification methods, this method is operationally simple and does not involve a complex modal processing procedure, which does not result in the loss of valid information.…”
Section: Of 23mentioning
confidence: 99%
“…In addition, it is noted that the H ε sr (ω) in Formula (11) takes into account the contribution of all the strain mode shapes. Under the premise that only the contribution of the ith-order strain mode shape is considered, Formulas (11) and (12) can be rewritten as:…”
Section: Second-order Strain Statistical Moments (Sssm)mentioning
confidence: 99%
“…Based on the vibration signal, a Shannon entropy-based methodology for detecting and locating a lost cable in a cable-stayed bridge exposed to ambient vibrations was presented by Jose et al [ 23 ]. A methodology based on statistical features, principal component analysis (PCA), and Mahalanobis distance (MD) for detecting and locating cable loss using vibration signals was proposed by Jesus et al [ 24 ]. These two methods were validated in the Rio Papaloapan Bridge (Veracruz, Mexico) with a 100% effectiveness to detect the lost cable location.…”
Section: Introductionmentioning
confidence: 99%
“…When working with rolling element bearing, Mathew and Alfredson [2] found that among more than twenty investigated statistical features, kurtosis is a damage-sensitive one that can provide a good indication of failure states. Yanez-Borjas et al [3] proposed to combine a set of statistical features, including high-order moments (up to 6 th ) and shape-related features, with the Principal Component Analysis algorithm and the Mahalanobis distance metric to perform SHM of load-bearing cables in a cable-stayed bridge. For SHM of wind turbines, root mean square is widely used as an effective parameter in identifying damage existence.…”
Section: Introductionmentioning
confidence: 99%